Structural and Electronic Heterogeneity of Two Dimensional Amorphous Silica Layers. Issue 7 (6th June 2014) - Altman, Eric I.; Schwarz, Udo D.
<x xml:space="preserve">Abstract</x> STM of amorphous silica bilayers reveals electronic heterogeneity between seemingly identical sites. The structure is constructed of 4–9 membered rings of corner sharing SiO4 tetrahedra. Certain oxygens bridging the larger rings vanish as the bias voltage is reduced while others bridging the same size rings are unaffected. The variation highlights the role of ring distortions in determining the local properties of this new 2D material. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>